Degradation of Authority and Institution of The Honorary Council Election - Jamil Jamil; Sholahuddin Al-Fatih (Faculty of Law, Mulawarman University, 2022)
This article discusses the position of the DKPP after the Constitutional Court Decision Number 32/PUU-XIX/2021 and the power of its decision. As is known, after the Constitutional Court Decision Number 32/PUU-XIX/2021, the DKPP Decision, which was originally final and binding, became unconstitutional if it was not interpreted as only binding on the President, KPU, Provincial KPU, Regency/City KPU and Bawaslu. The research method used is a legal research method using statutory approach, historical approach, and conceptual approach to be able to find new formulation of DKPP structuring design after Constitutional Court Decision Number 32/PUU-XIX/2021. The results of this study found that the weakening of the authority of the DKPP through the decision of the Constitutional Court Number 32 / PUU-XIX / 2021, should also be followed by the weakening of the DKPP institution, because after the final and binding character is weakened by the Constitutional Court, the DKPP no longer has the urgency to be used as a permanent institution. The Constitutional Court should affirm the institutional status of the DKPP as part of the institution exercising judicial power, so that the DKPP has a more definite status and its decisions remain final and binding.